Dapur Sehat, Anak Sehat: Pemberdayaan Masyarakat melalui Demonstrasi Memasak untuk Cegah Stunting - Alfi Fairuz Asna; Andi Trimulyono; Faik Kurrohman; Alya Fahimah Keisha; Christiana Natalia; Hasna Naurah Afkar; Berlian Arswendo Adietya; Maharani Citradewi; Paulina Anggita Sihaloho; Roja Roja (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Stunting is a public health issue caused by chronic malnutrition, particularly during the first 1,000 days of a child's life. In Demak Regency, reducing stunting prevalence remains a challenge that requires community-based approaches. Objective: This community services aims to enhance awareness and skills of mothers of toddlers in planning children's meals to prevent stunting Method: This community service program was conducted in Geneng Village, Mijen District, Demak Regency, aiming to empower pregnant women and mothers of toddlers through training and cooking demonstrations of supplementary feeding (PMT) using catfish as the main ingredient. The activities included problem analysis, material preparation, public outreach, and implementation of the training. Participants received hands-on training and a recipe book as supporting media. Result: The results showed increased knowledge and skills among participants in processing local food ingredients into nutritious meals that are appealing to children. The program also demonstrated potential to support household economies through home-based food production. Conclusion: This practice-based intervention proved effective in improving household nutrition resilience and represents a sustainable strategy for community-level stunting prevention.